Biosecurity, Health, Implementation - Salwa Khoirul Yaqin (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Sustainable beef cattle management system. The literature on biosecurity implementation, animal health tactics, and their effects on meat quality and productivity is reviewed in this article. The study was undertaken by analyzing many periodicals discussing disease prevention, animal welfare, and production efficiency. The analysis demonstrates that the installation of biosecurity can lower the risk of infectious diseases and increase cattle performance. The conclusion underlines the necessity to incorporate biosecurity and animal health as fundamental measures in modern livestock management.